Care leavers’ perspectives on the family in the transition from out-of-home care to independent living - Sting, Stephan; Groinig, Maria (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
Findings from youth research have shown that, due to the development of the transitional phase of “emerging adulthood”, the family has become increasingly significant for young adults as a source of support and as a safety net. In contrast, care leavers are confronted with a relatively abrupt transition to independent living. However, international studies have shown that the family also plays a significant role during the status passage of leaving care — as an arena of concrete social relationships, as a normative model and ideal, as a biographical experience and memory, as a connection to family traditions and practices, and as an important contextual factor for resilience and identity formation. The first section of this paper describes the various links between care leavers and their families based on a literature review. In the second section, the biographical relevance of the family is highlighted based on the example of a qualitative interview study about the educational pathways of 20- to 27-year-old care leavers. The study shows the various influences of family links on the educational careers of young people during and after out-of-home care. From the findings, we derive some consequences for professional work with families in out-of-home care and for professional support and guidance during the status passage of leaving care.